STUDI KERUSAKAN PRASARANA JALAN DI PASAR SENTRAL KALIBOBO KABUPATEN NABIRE TERHADAP AKTIVITAS EKONOMI MASYARAKAT - Semuel Rorroong D (Faculty of Engineering, Planning and Architecture, Winaya Mukti University, 2022)
Damage to roads will cause many losses to community activities or activities, especially economic activities that can be felt by users directly and also economic actors, in this case local market traders.Similar problems can be seen in road conditions in Kalibobo Central Market, Nabire Regency, Province Papua, in almost the last one period, the road at Kalibobo Central Market, Nabire Regency, is very concerned about. Many people have complained to the local Regency Government to pay attention to this road but until now it has not been well realized. The objectives of this study are: